C70 HIGH–SENSITIVE CARDIAC TROPONINS ELEVATION: NOT ONLY A CARDIAC DISEASE. ROLE OF HETEROPHILE ANTIBODIES. (18th May 2022) - Forzano, I; Campana, P; Ranieri, A; Sforza, A; Aversa, M; Musella, F; Basile, C; Perillo, E; Ciaramella, L; Tagliamonte, G; Sibilio, G
Abstract: Introduction: High–sensitive troponins I and T (hs–TnI and hs–TnT) represents the main biomarkers of Acute Coronary Syndrome diagnosis when combined with ST–T segment changes at ECG and typical clinical presentation. Elevated serum values of cardiac troponins can also be found in several cardiac diseases such as myopericarditis, pulmonary embolism and heart failure, conversely also in non–cardiac diseases. Among them, the analytical interference due to heterophile antibodies (HA) represent a rare non–cardiac cause of troponins elevation. Case Presentation: We report a case of a 20–year–old man admitted to our Cardiology department for palpitations and dyspnea, associated with persistently high levels of TnI–HS. He presented no cardiovascular risk factors. During hospitalization the patient was asymptomatic with persistent TnI–HS elevation (1051.4 pg/mL; r.n. 0–34 pg/mL) associated with no CK–MB values changes or typical rise and fall of myocardial damage biomarkers at lab test. Cardiac magnetic resonance excluded myopericarditis or cardiomyopathies in this patient, therefore HA capture test was performed using HA blocking tube reagents. The analytical interference due to HA has been identified with a post–test hs–TnI value of 16.9 pg/mL. Conclusions: The analytical interference due to HA is a rare and underestimated cause of false–positive results in cardiac troponin essay, however it should be excluded mostly in young patients without cardiovascular risk factors. Persistent hs–TnI and hs–TnT elevation combined with the absence of typical rise and fall of cardiac troponins and with no CK–MB alterations should help the clinician to recognize this analytical phenomenon at the emergency department.